PENGARUH LATIHAN MEDICINE BALL TERHADAP POWER OTOT LENGAN ATLET PUTRA CLUB PB BANK RIAU KEPRI PEKANBARU - Abdul Razak; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The problem in this research is stepping in to perform basic punches such as drop shot, net, drive and smash. Only the strength of the arm and shoulder muscles does not look good, this can be seen during the jump smash. there are still many balls that do not pass the net. This type of research is an experiment with the One-Group Pretest-Posttest Design approach. The purpose of this research was to determine the effect of leg muscle strength. The population in this research consisted of 8 male athletes PB Bank Riau Kepri. The sampling technique uses total sampling, where the total population is sampled. The data collection technique was obtained from the pre-test and the post-test. The instrument in this research used the ambidextrous madicin ball put test as a tool to measure the strength of the arm muscles. Pre-test results data after the LoMax calculation is 0.107 and Ltable is 0.285. It can be concluded that the distribution of muscle strength data from the pretest is normally distributed. For muscle strength testing after the test, the LoMax is 0.163 and the Ltable is 0.285. This means that LoMax is smaller than LTabel. It can be concluded that the distribution of posttest data is normally distributed. The analysis of the t-count between the shore test and the final test number is 5.812 and compared to the t-table value at a significant level of 0.05 degrees of freedom, it appears to be N - 1 (7) 1,895, showing that the tcount (5,812)> t table (1,895), It can be concluded that the hypothesis that there is an effect of medicine ball training on arm muscle strength in male athletes is PB Bank Riau Kepri Pekanbaru.Key Words: Madicine Ball Exercise, Arm Muscle Power, Badminton